Leadership in the Age of Artificial Intelligence in Elementary Education Management - Mohammad Bilutfikal Khofi; Lahij Kamal; Nawal Nur Arafah (Journal of Elementary Education Research and Practice, 2026)
The rapid development of Artificial Intelligence (AI) has transformed educational leadership practices, including at the elementary school level, which raises distinctive pedagogical and ethical considerations. This study aims to examine AI-based educational leadership in elementary education, emphasizing the balance among data utilization, pedagogical wisdom, and humanistic values. A Systematic Literature Review (SLR) was conducted by analyzing peer-reviewed articles published between 2015 and 2025 that address educational leadership, AI, and primary education. The findings indicate that AI significantly supports data-driven leadership by enhancing responsive and evidence-based decision-making; however, it cannot replace the role of school principals as interpreters of data who consider students’ social-emotional development and the unique context of elementary education. The successful implementation of AI is also highly dependent on establishing teachers’ psychological safety, fostered by supportive, ethical leadership that encourages reflective adaptation to technology without undermining professional autonomy. Furthermore, AI has strong potential to support differentiated and inclusive learning, provided it is managed fairly and does not lead to labeling or learning inequalities. This study underscores that elementary school leadership in the AI era must be grounded in a strong ethical commitment to child protection, equity, and inclusivity, positioning AI as a means to strengthen educational practices rather than an end in itself.